Basement-controlled structural fronts forming an apparent major refold pattern in the Yellowknife domain, Slave Province - Fyson, W. K. (Canadian Journal of Earth Sciences, 1984)
Trend lines of tight folds (F 0 and F 1 ) in Archean metasediments curve across the Yellowknife supracrustal domain to form an apparent major refold pattern. "Hinge traces," marking pronounced changes in trend, extend up to 50 km. More locally, F 1 folds are discontinuous and markedly discordant in trend, suggesting that the major hinge traces, rather than simply following axial surfaces, denote structural fronts where fold sets with distinctive initial trends have interacted.Cleavages grouped as S 2 and S 3 , each with subsets, postdate the F 1 , folds. A regional S 3 cleavage strikes parallel to major hinge traces, whereas discontinuous S 3 subsets are oblique, some terminating along well defined cleavage fronts. For example, one subset replaces another along a front generally parallel to a hinge trace, or fold front, but offset 1–2 km.The development of the apparent refold pattern and the parallelism of various generations of structural fronts and cleavages can be explained by the response of cover rocks to recurrent strike-slip movements and stress reorientations by faults in the basement.